Implementation Of The 9P Sharia Marketing Mix Strategy In The State Of Tourism In The State Of Jahetan Layar Kutai Lama, Anggana District, Kutai Kartanegara Regency - Irma Yuliani; Mahmud Al Chusairi (CV. Ulil Albab Corp, 2025)
East Kalimantan has the potential for world tourism that is no less interesting. Good tourism management is very important to be carried out through the implementation of reliable marketing strategies that create a beneficial relationship for both parties as applied to the Jahetan Layar Kutai Lama Country Tourism, Anggana District, Kutai Kartanegara Regency.which is a leading tourist destination in Anggana District, offers the natural beauty of the mountains, the Mahakam River, and authentic Dayak culture as one of the leading tourist destinations that have Beautiful panorama is equipped with interesting rides and good facilities. Sharia marketing is a business that leads to creating and offering value change in accordance with Islamic contracts and the principle of muamalah through the 9P Marketing mix, namely Product, Price Place, Promotion, People, Process, Physical Evidence, Promise, Patience. This study aims to find out the implementation of sharia marketing strategies through the 9P marketing mix applied and its impact and constraints on tourism. The type of research used is qualitative research. This research is a field research using primary and secondary data using data collection techniques through observation, interviews and documentation with resource persons from managers such as owners, staff and employees, the anggana sub-district government, and tourist visitors. The data analysis techniques used through Triangulation are data reduction, data presentation, and conclusion drawn. The results of the manager's research use a sharia marketing strategy with a 9P marketing mix which shows that the manager focuses on quality products such as camping rides, trekking, atv and trail motorcycles, cafes/restaurants, photography spots, villas, transparent and competitive prices, strategic locations presenting scenery with beautiful panoramas, promotion through the distribution of brochures, social media such as TikTok, Instagram and Facebook., friendly and patient service and willing to receive suggestions and input, supported by skilled employees drawn from the local community, processes that are organized according to standards, and physical evidence in the form of adequate facilities for clean and comfortable prayer rooms for worship, trustworthy and keeping promises to provide the best service. Cooperation with the Tourism Office and Travel Agents to Strengthen the Promotion of Destinations Must Be Increased Although this tourist location is far from the city center, this tourism is able to create economic opportunities for the local community through the provision of jobs, empowerment of MSMEs, and tourism activities. This place is also a place for family recreation, a place to gather to establish friendship and is ideal as a forum for office activities. The manager hopes for government support to improve infrastructure, facilities, and tourist attractions. With sustainable management, this destination has the potential to become a tourism icon in East Kalimantan that supports cultural and environmental preservation and encourages economic growth.